Historia da Egreja Catholica em Portugal - Amado, Jose de Sousa (na Typographia De G. M. Martins, 1871)
Stamp of St. Joseph Seminary
Keywords: 1.Conservation 保護; 10.Cover Damage; 18.Bookworm; 2.Damage